Non-Revenue Water (NRW) for sustainable university campuses: a review / Wan Nur Syazwani Wan Mohammad - Wan Mohammad, Wan Nur Syazwani (Universiti Teknologi MARA, Perak, 2023)
Non-revenue water (NRW) is the difference between the supplied and the billed quantity due to apparent and real losses. A higher rate of NRW reflects higher revenue loss to the state. The NRW cannot be totally avoided, thus understanding, and managing its components is very vital. Of late, research on NRW particularly on University Campuses is still an emerging field. Hence, this paper delineates the overview of NRW, a sustainable University Campus, and the benefits of NRW in the University Campus' sustainability. To do so, an extensive literature review via three main databases (ie., Web of Science, Science Direct, and Scopus) was conducted. From the review, six (6) aspects of NRW (ie., NRW prediction or estimation, the water distribution network, digital tools, NRW management, driver of water losses, and costeffectiveness of NRW) were discussed in the previous study. While, four (4) categories (i.e., water quality, customer complaints, water resources, and impact on service efficiency and financial management) are listed as benefits of NRW through the NRW reduction program in the sustainability of the University Campus. As a result, this paper is able to provide insight to University Stakeholders for the consideration of NRW in managing water management for sustainable campus development.